How do people feel while walking in the city? Using walking-triggered e-diaries to investigate the association of social interaction and environmental greenness during everyday life walking - Bollenbach, Lukas; Schmitz, Julian; Niermann, Christina; Kanning, Martina (Frontiers in Psychology, 2022)
Background: Light to moderate physical activity, which includes walking, is associated with positive effects on physical and mental health. However, concerning mental health, social and physical environmental factors are likely to play an important role in this association. This study investigates person-place interactions between environmental characteristics (greenness, social interaction) and momentary affective states during walking episodes. A within-subject design is implemented, in which affective states and environmental characteristics are assessed while participants are walking outside. Methods: On smartphones, coupled with a motion sensor (move3), e-diaries were triggered as soon as people walked 100m outside. E-diaries assessed momentary affective states (valence, calmness, energetic arousal), and social interaction (walking alone; seeing other people while walking; interacting with other people; walking with a known person) between 6 am and 10 pm over nine days. The percentage of greenness was determined afterward from recorded GPS and GIS data. Demographics were collected in advance via an online questionnaire. Multilevel models were calculated with R for 46 individuals (age = 41.2, ± 13.2; 52% female). Results: Affective state dimension energetic arousal showed a significant association with social interaction and greenness, i.e., participants rated energetic arousal lower when walking alone, and if there was less greenness vs when interacting shortly with someone while walking (β = 0.13, p = 0.02), and being in situations with more greenness (β = 0.08, p = 0.02). Furthermore, associations with social interaction and greenness were found for dimension calmness: walking together with someone was associated with higher calmness (β = 0.16, p = 0.02), and the higher the proportion of surrounding greenness during a walk, the higher calmness was rated, i.e., participants were calmer (β = 0.09, p = 0.01). Significant associations with valence were not present. Conclusions: The findings indicate that the affective states varied significantly due to different social and physical environmental factors. In the future, the importance of environmental factors should be further investigated, e.g., by assessing environmental factors right in situations contrary to a subsequent imputation. Within-subject designs, and in particular triggered assessments with the addition of GPS, can aid in developing interventions for health-promoting urban environments.